New approach for finding basic performance measures of single server queue - Koh, Siew Khew; Pooi, Ah Hin *; Tan, Yi Fei (Hindawi Publishing Corporation, 2014)
Consider the single server queue in which the system capacity is infinite and the customers are served on a first come, first served basis. Suppose the probability density function